Penggunaan Metode Human-Centered Design dalam Perancangan Pengalaman Pengguna Aplikasi Sistem Informasi UMKM Kelurahan Cacaban Kota Magelang - Vito Kurniawan Sampurno; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Cacaban is a neighborhood in the city of Magelang with a variety of small and medium enterprises (SMEs). The Industry and Trade Department plays a role as a stakeholder. Through interviews, SME traders agree that there should be a platform that can help promote their business products. In addition to traders, consumers also play a role in achieving maximum results. This research designs an SME information system application using the human-centered design method because it involves humans as users in terms of needs and behavior. The result of this research is a mobile application mock-up. Evaluation involves usability testing and user experience. The results indicate a 100% rate for the effectiveness aspect of usability testing for both user groups, consumers, and traders. The average efficiency aspect of the usability testing result for the consumer group is 0,37 seconds from a total of three tasks, while for the trader group it is 0,72 seconds from a total of five tasks. The average satisfaction aspect of the usability testing result among the four parameters for the consumer group is 86%, while for the trader group it is 91%. The results of user experience measurement for the consumer group were in the "good" and "excellent" categories, but in the novelty aspect, there was a decrease to "below average", because the participants felt that the application was like existing competing applications. The results of user experience measurement for the trader group were in the "good" category.